Content analysis of qualitative information, El Alcázar (1928-93). An institutional approach - Moreno Aguayo, Alonso (De Computis, Revista Española de Historia de la Contabilidad., 2012)
Our research examines the information provided by a private Spanish company, the brewery El Alcazar, on the changes that occurred in the period 1928-93, with the aim of of advancing knowledge of accounting through historical analysis, and studying the organisation’s dependencies on its dependencies of the organisation with its environment. More specifically, we applied the analysis of of content to the evolution of the external information, the "Report", i.e. the qualitative information contained in the annual report, which is in fact a management report (MI) for shareholders, and internal information, i.e. the minutes of the Board of Directors (BOD) and the minutes of the General Meeting of Shareholders (AGM). We analysed them with the aim of studying whether the content of the documents is adapted to the different institutional environments through which the company has passed.